The Racism Resistance in Django Unchained Movie: Main Character - Cicih Nuraeni; Adhytia Nugraha Aria S.A (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2022)
The purpose of this paper is to determine the types of racism that occur in the Django Unchained movie and the impact of racism on black people. Racism is defined as a physical, verbal, or emotional act by a white person who feels superior to black people and uses them as slaves. The writers collects data using a descriptive qualitative method with sources from dialogues and scenes the original Django Unchained Movie. The writers watched this movie several times to strengthen the analysis and conducted library and internet research to add supporting data. The findings of this study are as follows: (1) Individual Racism-Level and Cultural Racism are the types of racism cases found in the film Django Unchained. (2) The effects of racism on black people include feelings of fear, vengeance, anger, and depression. The moral messages conveyed by this film are as follows: human race equality, the importance of mental health, and solidarity or respect for one another. This study reveals that racism in the film Django Unchained can occur anywhere and at any time, and that there are currently many racism cases in many countries.